Critical Thinking Skills of High School Students in Biology Learning on the Concept of Structure and Function of Plant Tissues - Heny Kustiani; Muhammad Zaini; Mulyadi Mulyadi (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
One of the problems faced in education in the 21st century is the critical thinking skills of students who are still considered lacking. One of the learning tools that need to be improved to help improve students' critical thinking skills is the Student Worksheet (LKPD). This study aims to describe the effectiveness of LKPD on the concept of Structure and Function of Plant Tissue Based on Critical Thinking Skills. The validation subjects were 3 experts, individual test subjects were 3 high school class XI students and small group test subjects were 6 class XI high school students. This type of research is development research to produce valid, practical, and effective products. The results showed that the effectiveness of LKPD expectations based on the assessment of students' critical thinking skills in working on LKPD had both categories (including interpretation, analysis, inference, and explanation) and very good categories (including self-regulation). Interpersonal skills (collaborating) and intrapersonal skills (meticulous) students have very good categories.AbstrakSalah satu permasalahan yang dihadapi dalam pendidikan pada abad ke-21 ialah keterampilan berpikir kiritis (KBK) peserta didik yang dianggap masih kurang. Salah satu perangkat pembelajaran yang perlu diperbaiki untuk membantu meningkatkan keterampilan berpikir kritis peserta didik ialah Lembar Kerja Peserta Didik (LKPD). Penelitian ini bertujuan untuk mendeskripsikan keefektifan LKPD pada konsep Struktur dan Fungsi Jaringan Tumbuhan Berbasis Keterampilan Berpikir Kritis. Validator adalah 3 orang ahli, subjek uji perorangan adalah 3 orang peserta didik kelas XI jenjang SMA dan subjek uji kelompok kecil adalah 6 orang peserta didik kelas XI jenjang SMA. Jenis penelitian ini merupakan penelitian pengembangan untuk menghasilkan produk yang valid, praktis, dan efektif. Hasil penelitian menunjukkan bahwa keefektifan harapan LKPD berdasarkan penilaian keterampilan berpikir kritis peserta didik dalam mengerjakan LKPD memiliki kategori baik (meliputi interpretasi, analisis, inferensi dan eksplanasi) dan kategori sangat baik (meliputi pengaturan diri). Keterampilan interpersonal (bekerjasama) dan keterampilan intrapersonal (teliti) peserta didik memiliki kategori sangat baik.